(untitled) (Analysis in Theory and Applications, 2017)
In this paper, we deal with the complex Baskakov-Szász-Durrmeyer mixed operators and study Voronovskaja type results with quantitative estimates for these operators attached to analytic functions of exponential growth in D_R={z∈C;|z|